Contemporary Switzerland Revisiting the Special Case - Kriesi, H.; Farago, P.; Kohli, M.; Zarin-Nejadan, M.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2005)
This volume presents the major findings involved in a large scale research programme to describe and analyse the transformation of contemporary Swiss society. The contributions focus on three key areas: the Swiss way of life, the Swiss labour market and the country's political institutions. The chapters give an idea of current trends in Swiss society, each one framing their argument in a comparative perspective.
Keywords: Economic policy; Political economy; International relations; International economics; Economic Policy; International Political Economy; International Relations; International Economics